2013
DOI: 10.1007/s00595-013-0787-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring of serum p53 antibody after neoadjuvant chemotherapy and surgery for esophageal adenocarcinoma: report of a case

Abstract: We monitored serum p53 antibody (s-p53-Ab) titers in a 76-year-old man with esophageal adenocarcinoma, clinical stage III (T2N2M0), for over 4 years, including during the perioperative period and throughout follow-up after surgery. Screening tests for CA19-9 (205 IU/ml) and s-p53-Abs (381 U/ml) were positive before treatment. After neoadjuvant chemotherapy with 5-FU and cisplatin, CA19-9 decreased to the normal range, but the s-p53-Ab titer remained positive (224 U/ml). Pathological findings of surgically rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Some IgG autoantibodies have been found to respond to tumor-associated antigens in the sera of patients with cancer, even at the early stages (6,7). Since RalA is a tumor antigen, autoantibodies against RalA (s-RalA-Abs) have been reported as potential biomarkers for hepatocellular (8), esophageal (9), colorectal (10), breast (11) and ovarian (12) carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Some IgG autoantibodies have been found to respond to tumor-associated antigens in the sera of patients with cancer, even at the early stages (6,7). Since RalA is a tumor antigen, autoantibodies against RalA (s-RalA-Abs) have been reported as potential biomarkers for hepatocellular (8), esophageal (9), colorectal (10), breast (11) and ovarian (12) carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was not enough evidence of s‐p53 Abs in esophageal adenocarcinoma, a few papers have shown that s‐p53 Abs seem to be useful in detecting esophageal adenocarcinoma with p53 overexpression …”
Section: S‐p53 Abs In Patients With Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…The G 1 check point represents the major machinery for responding to DNA damage and is regulated by the p53/MDM2-p21 pathway, which is capable of inducing sustained and sometimes permanent G 1 arrest (2). The G 1 checkpoint involves two critical tumor suppressors governed by p53 and RB, both of which represent major mechanisms commonly deregulated in many human cancers (3,4).…”
mentioning
confidence: 99%